Pengaruh employee engagement dan lingkungan kerja terhadap motivasi kerja karyawan di divisi Human Capital Management Bank XYZ - Kristanti, Christy; Lutfi, Anas (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
The purpose of this research is to examine whether employee engagement and work environment can influence work motivation. The populations of this research are employees at Bank XYZ and the samples are employees in the Human Capital Management division. The number of employees in Human Capital Management is 156. The samples are collected from 148 respondents via online questionnaires with the non-probability sampling technique with the purposive sampling method. The analysis technique used is multiple linear regression with the supported application SPSS 23 version. The result from data analysis showed that employee engagement affected work motivation.